PEMODELAN DAN SIMULASI SISTEM KEMUDI EMPAT RODA DAN PENGONTROLANNYA DENGAN METODA LINIER QUADRATIK GAUSSIAN - Sampurno, Bambang
Abstract : The Four wheel steering is steering mechanism that use for their four wheel in the cornering. Usually the four wheel steering (4WS) use to improve menuverability at low-medium speed (<35km/h) and improve stabilability at. medium-high speed (>35km/h). In this research the four wheel steering is divided to three kind open loop four wheel steering: (4WMB), four wheel steering with yaw-sate feedback for the rear command (4WST) and optimal control four wheel steering. In the steady-state cornering the matematic models of vehicle are made when speed and steering angle are kept constant with rough and level road surface asumption. At low-medium speed produce two of dyamics equilibrium are lateral force and yawing moment direction. While at medium high speed produce three of dynamics equilibrium are lateral force, yawing moment and rolling moment direction. But Lee AY (1995) made matematical models of vehicle at medium-high speed have two of dynamics equillibrium are lateral force and yawing moment direction with flat and level asumption. This matematical models produce system stability for 4WSB and 4WST system. The simulation on all of four wheel steering models be done with longitudinal speed input is impulse and steering angle are impulse and half sinusoidal wave. Optimal control four wheel steering with estimation state space be done with system and measurement disturb asumption are white noise. From this reasoning be designed optimal control with Linier Quadratic Gaussian (LQG) method and it use Kalman Filter estimator. The simulation results of lateral velocity and yaw-rate output at low-medium speed have systems atabil characteristic for 4WSB and 4WST system. Optimal control in this speed use to reduce settling time of output. The difference of lateral velocity settling time between before and after system be controlled are large number for all input. There are about 20 seconds before system be controlled and about 1 seconds after be controlled The simulation results of lateral velocity, yaw-rate and roll-rate output at medium high speed have trend to not stabil for 4WSB and 4WST system. There for design of optimal control is very significant for system stabilisation. All of output settling time are about 3 seconds for input longitudinal speed and about 8 seconds for input steer angle.